ANALISIS FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA (12-59 BULAN) DI PUSKESMAS SUKADIRI KABUPATEN TANGERANG TAHUN 2018 - Bunga Tiara Carolin; Anggita Rizki Saputri; Vivi Silawati (Jurnal Ilmu dan Budaya, 2020)
Background: Nutrition Status Monitoring in 2018 organized by the Ministry of Health states that the percentage of malnutrition in infants aged 0-59 months in Indonesia was 3.8%, while the percentage of malnutrition was 14%. Nutritional needs for children in the early days of life are very important. Malnutrition can have bad consequences even death. Objective: To determine the analysis of factors that affect the nutritional status of toddlers (12-59 months) in Sukadiri Health Centre Tangerang Regency in 2018. Methodology: The design of this study is an analytical survey using a cross sectional approach. The sample in this study were 97 toddlers. Instrument consists of KMS and questionnaire. Data were analyzed using Chi Square test to determine whether or not there is a relationship between the independent variables and the dependent variable. Results: Of the 97 toddlers, most of the toddlers had good nutrition status which was 72.2%, toddlers who received exclusive breastfeeding was 53.6%, toddlers who had infectious diseases was 53.6%, maternal behavior in providing good food for toddler was 55.7%, good environmental sanitation was 51.5%, Chi Square test results obtained history of exclusive breastfeeding (p value = 0.116), history of infectious diseases (p value = 0.014), maternal behavior in feeding toddlers (p value = 0.002), environmental sanitation (p value = 0.022). Conclusions: From this study it was found that there was a significant relationship between history of infectious disease, maternal behavior in feeding toddlers, and environmental sanitation but there was no relationship between exclusive breastfeeding history and nutritional status of toddlers.